Spontaneus pregnancy after obstructive nabothian cyst treatment - Turan, Gökçe; Yalcin Bahat, Pinar; Aslan Çetin, Berna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Nabothian cysts are common and silent retention cysts of the uterine cervix with no particular intervention required. It is quite rare to reach a size of more than 4 cm and it is a diagnostic dilemma to differ it from adenoma malignum. Here we report a case a woman who conceived after 3.5 cm of naboth cyst treatment.